Pengaruh safety climate tehadap keselamatan kerja: safety behavior sebagai variabel pemediasi - umam, hafilan zainul; faidal, faidal (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
The aim of this study to determine the effect of safety climate and safety behavior on work safety. This research was conducted at PT. Sumekar in Sumenep Regency. The method research uses quantitative methods. The population of this research is 150 employees with a sample size of 60 employees which is determined based on Slovin’s formula. The data analysis used in this study is a statistical product of SPSS. The results obtained from this study indicate that (1) safety climate has an effect on work  safety with a significant value of 0.000 0.05. (2) Safety climate influences safety behavior with a significant value of 0.000 0.05. (3) Safety behavior has an effect on work safety with a significant value of 0.021 0.05. And (4) safety climate affects work safety through safety behavior with a significant value of 0.000. Keywords: safety behavior; safety climate;  work safety.